DEVELOPMENT OF RECOMMENDATIONS FOR MANAGEMENT OF THE GEOMECHANICAL PROCESSES IN THE CONSTRUCTION OF UNDERGROUND STRUCTURES IN SYRIA - D L Neguritsa; Khalil Said Alafar (RUDN Journal of Engineering Research, 2016)
In the article present the composition of methods for managing geomechanical processes in the construction of underground structures on swelling clay soils. It was shown that the main methods to management geomechanical processes in the construction of underground structures consist in the regulation of ground water exchange with the environment. The activities, eliminating or reducing the strain of foundations on swelling soils. Protection measures to solve the issue of reducing the influence of deformation of the base of the underground structures and prevent damage to buildings and structures built on swelling soils.